Răspuns :
a - b = 72
a: b = 7
a = 7b
7b - b = 72
6b = 72
b= 72:6
b = 12
a = 7 x 12 = 84
84- 12 =72
84:12 = 7
a: b = 7
a = 7b
7b - b = 72
6b = 72
b= 72:6
b = 12
a = 7 x 12 = 84
84- 12 =72
84:12 = 7
Fie a si b cele doua numere.
a:b=7 =>a=7×b
a-b=72
Il luam pe "a" din prima relatie si il vom inlocui in a doua relatie:
a-b=7b-b=72
=>6b=72
b=72:6=12
=>a=7×b=7×12=84
Verificare: a-b=84-12=72
a:b=7 =>a=7×b
a-b=72
Il luam pe "a" din prima relatie si il vom inlocui in a doua relatie:
a-b=7b-b=72
=>6b=72
b=72:6=12
=>a=7×b=7×12=84
Verificare: a-b=84-12=72